2022
DOI: 10.3390/su14159579
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Innovation and Firm Performance: Evidence from South America

Abstract: Eco-innovation has received a great deal of attention in academia and the business sector because it promotes a firm’s sustainable development and seeks to improve its performance. The prime objective of this study was to analyze the effect of the process, organization, and product eco-innovation on the company’s financial and environmental performance. Using a structural equation model estimated by maximum likelihood and a sample from 214 South American manufacturing companies in Colombia, Ecuador, and Perú, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Our results support the prediction of H1, consistent with previous findings that green design is a useful tool for improving organizational performance (Almeida and Wasim, 2022; Barriga Medina et al , 2022; Wang and Sarkis, 2013).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Our results support the prediction of H1, consistent with previous findings that green design is a useful tool for improving organizational performance (Almeida and Wasim, 2022; Barriga Medina et al , 2022; Wang and Sarkis, 2013).…”
Section: Resultssupporting
confidence: 92%
“…This hypothesis is supported by Doran and Ryan (2012), Wang and Sarkis (2013), and Lee (2015). In the South American region, Barriga Medina et al (2022) reported a significant positive relationship between eco-innovation and performance in a sample of 214 manufacturing companies in Colombia, Ecuador, and Peru. However, Filbeck and Gorman (2004) and Brännlund and Lundgren (2010) suggest a contrary relationship and argue that “green” investments reduce profitability for most firms.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, in the context of climate change accompanied by limited natural resources, it is of particular importance to implement measures that strengthen energy security by developing environmentally friendly processes through the transition to green energy, sustainable and smart city mobility, and optimization of agro-biomass supply chains that include the production, promotion and consumption of environmentally friendly products and services. Creation of a system for managing climate-neutral investment projects is considered through the lens of developing and implementing eco-innovations with an environmental and economic effect, for instance, the impact of environmental innovations on the operation, organization, marketing, financing, and environmental performance of the company (Barriga Medina et al, 2022). It is therefore important to ensure investment support for the innovative development of municipal transport infrastructure on the basis of climate neutrality and energy efficiency, namely building a network of charging stations for electric vehicles, bicycle paths, and amassing a fleet of ecological public transport.…”
mentioning
confidence: 99%